ANALISIS MINAT PENGGUNAAN UANG ELEKTRONIK TERHADAP MAHASISWA AKUNTANSI UNIVERSITAS MUHAMMADIYAH MAKASSAR - Muchran, Muchriana; Putriani, Dhiza; Adesty, Adesty; Ramadhani, Diva Novita (IJMA (Indonesian Journal of Management and Accounting), 2024)
This research aims to determine and analyze the influence, compatibility effect, complexity, perceived usefulness, social influence and trust in students' interest in using electronic money. The research used to test the analysis of interest in using electronic money among accounting students at Muhammadiyah University of Makassar is a quantitative approach. This research uses primary data, namely data obtained directly from the research object. The data collection technique uses a questionnaire distributed to accounting students at Muhammadiyah University of Makassar. The data analysis techniques used are validity tests, reliability tests, correlation tests, multiple regressive analysis and t tests. The research results from multiple linear regression analysis, partial results (t-test) show that compatibility (X1), complexity (X2), perceived usefulness and social influence (X4) have a significant positive influence on interest in using electronic money and trust (X5). The negative effect on interest in using electronic money (Y1) is not significant.